2008
DOI: 10.1130/b26254.1
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope constraints on the elevation history of the Sierra Nevada Mountains, California

Abstract: Research on the uplift history of the Sierra Nevada mountain range has yielded seemingly confl icting results. Some studies argue for substantial uplift within the past 3-5 m.y.; others suggest that high elevations may have existed since the Cretaceous. The rain shadow across the Sierra Nevada is associated with a strong isotopic gradient, with lower δ 18 O values in precipitation on the leeward side of the range. Reconstruction of the δ 18 O value of meteoric water as a monitor of paleoelevation has focused m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 77 publications
4
26
0
1
Order By: Relevance
“…8; Wolfe et al, 1997;Horton and Chamberlain, 2006;Mulch et al, 2006;Crowley et al, 2008;Cassel et al, 2009aCassel et al, , 2009bCassel et al, , 2010Hren et al, 2010), although Molnar (2010) contested the signifi cance of the isotopic data. Based on estimates of crustal thickness and analogy to the Altiplano of the Andes, Best et al (2009) interpreted a paleodivide at an elevation of ~4 km.…”
Section: Absolute Elevationmentioning
confidence: 95%
“…8; Wolfe et al, 1997;Horton and Chamberlain, 2006;Mulch et al, 2006;Crowley et al, 2008;Cassel et al, 2009aCassel et al, , 2009bCassel et al, , 2010Hren et al, 2010), although Molnar (2010) contested the signifi cance of the isotopic data. Based on estimates of crustal thickness and analogy to the Altiplano of the Andes, Best et al (2009) interpreted a paleodivide at an elevation of ~4 km.…”
Section: Absolute Elevationmentioning
confidence: 95%
“…This widespread peneplain stood high, judging from stable isotope palaeoelevation studies (Horton et al 2004;Horton and Chamberlain 2006;Mulch et al 2006;Crowley et al 2008). Its surface was covered in late Miocene time by a series of lahars, trachyandesites, basaltic lava flows, and associated volcanogenic sediments that extended EW across the ranges for , 200 km; this hinterland was then normal-faulted, uplifted, and dissected by more recent erosion (Jayko 2009;Van Buer et al 2009).…”
Section: Introductionmentioning
confidence: 97%
“…A similar pattern of elevation change was claimed by Wolfe et al (1997) using palaeobotanical data. Crowley et al (2008) analysed oxygen isotopes in mammalian tooth enamel and concluded that a Sierran rain-shadow had existed since at least 16 Ma. Kent-Corson et al (2006) conclude there is a growing body of evidence for a migration of high surface elevation from the northern to the southern Great Basin from the late Eocene to the Miocene.…”
Section: Palaeoaltitude Of the Great Basin Areamentioning
confidence: 99%